2023
DOI: 10.1021/acsinfecdis.3c00051
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic and Functional Characterization of Eosinophil and Migratory Dendritic Cell Subsets during Filarial Manifestation of Tropical Pulmonary Eosinophilia

Abstract: The role of eosinophil and migratory dendritic cell (migDC) subsets during tropical pulmonary eosinophilia (TPE), a potentially fatal complication of lymphatic filariasis, has not been explored. We show that the onset of TPE is characterized by the accumulation of ROS and anaphylatoxins and a rapid influx of morphologically distinct Siglec-Fint resident eosinophils (rEos) and Siglec-Fhi inflammatory eosinophils (iEos) in the lungs, BAL fluid, and blood of TPE mice. While rEos display regulatory behavior, iEos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The NPA gene have not been annotated previously from any nematode parasites, and this this is the first report on a pan allergen. IgE, eosinophils and allergy are hallmarks of nematode parasitic infections and TPE [31]. We believe that the NPA could play a major role in triggering the allergic responses in the host during parasitic larval invasion.…”
Section: Discussionmentioning
confidence: 91%
“…The NPA gene have not been annotated previously from any nematode parasites, and this this is the first report on a pan allergen. IgE, eosinophils and allergy are hallmarks of nematode parasitic infections and TPE [31]. We believe that the NPA could play a major role in triggering the allergic responses in the host during parasitic larval invasion.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, Gang et al recently demonstrated that a similar increase in inflammatory eosinophils occurs in the TPE Brugia spp . model [ 55 ], which could indicate that these eosinophils might be associated with lung hyper-responsiveness, MF clearance and potentially lung pathology. Accordingly, tissue repair mechanisms, i.e., release of AREG and enhanced matrix metalloprotease activity in ELD mice of our study suggest that the loss of lung tissue integrity could be caused by a prolonged repair mechanism and fibrosis which was dependent on eosinophils and IL-33 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The NPA gene have not been annotated previously from any nematode parasites, and this this is the first report on a pan allergen. IgE, eosinophils and allergy are hallmarks of nematode parasitic infections and TPE [ 32 ]. We believe that the NPA could play a major role in triggering the allergic responses in the host during parasitic larval invasion.…”
Section: Discussionmentioning
confidence: 99%